Enterovirus 71 CNS Infection and ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
ADHD symptoms as long-term sequelae of virus-confirmed enterovirus 71 infection were evaluated in 86 children, aged 4 to 16 years, followed at National Taiwan University Hospital, Taipei, and Chang Gung Children's Hospital, Taoyuan, Taiwan.